Reporting on software development projects to senior managers and the board. - Oliver, G. R.; Walker, R. G. (Abacus, 2006)
It is contended that the scale of some in-house software projects (and the potential impact of project failure on an organization's operating capabilities and reputation) is such that the progress of those projects warrants the concentrated attention of senior managers (and possibly, the Board). The article utilizes a case study to illustrate how the adoption of key proposals outlined in the business information systems and software engineering literatures for the management of these projects may not necessarily be effective. This work augments Walker and Oliver (2005 ), which examined the options when accounting for software expenditure and recommended expensing for consistent treatment. This article then reviews the ‘information needs’ of senior managers, and presents a set of six reporting templates to facilitate the effective monitoring of progress of software projects (including post-migration expenditure on system enhancements and maintenance, and efforts to capture planned benefits). In some circumstances, the scale and risks associated with software development projects warrant oversight of these projects by the Board, possibly through the establishment of specialist ‘IT governance’ subcommittees. Accordingly, a model charter for an IT governance committee is presented in an appendix.